Epidemiology of Cardiovascular Disease in Patients with Type 1 Diabetes: European Perspective - Matteucci, E.; Giampietro, O. (Experimental and Clinical Endocrinology & Diabetes, 2014)
The International Diabetes Federation estimated that 5.1 million people aged between 20 and 79 years died from diabetes in 2013, accounting for 8.4% of global all-cause mortality among people in this age group. Type 1 diabetes is associated with a 2- to 4-fold increased mortality risk compared with the general population. Before the onset of late complications, most of the excess mortality is from potentially preventable causes of death such as ketoacidosis, whereas the long-term excess mortality is largely due to cardiovascular disease. However, a wide geographic variation in mortality of type 1 diabetic patients has been evidenced and accurate estimates of mortality attributable to diabetes are difficult to obtain. The review provides an overview of currently available evidence and summarizes main problems in estimating early and long-term mortality by cause of death in type 1 diabetes, paying particular attention to European studies.
Keywords: diabetes mellitus type 1; mortality; cardiovascular disease; Europe